Evaluation of the relationship between shear wave elastography measurements with laboratory and Doppler US parameters in patients with adult Hashimoto?s thyroiditis - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Background/aim: Hashimoto thyroiditis (HT) is an autoimmune disease that leads to tissue stiffening secondary to lymphocyte infiltration of the thyroid gland. Gray-scale ultrasound (US) is widely used in its diagnosis. Numerous studies have been conducted comparing elastography findings of HT with tissue stiffness and immunoreactivity levels. This study aims to reveal the relationship between shear wave elastography (SWE) and Doppler parameters in patients with HT. Materials and methods: The study group consisted of 45 patients diagnosed with HT, and 20 control patients without thyroid pathology. Thyroid-stimulating hormone (TSH) and antithyroid peroxidase (TPO) values were examined in patients with HT. Thyroid gland volume and echo patterns were evaluated in the gray-scale US. Doppler measurements-peak systolic velocity (Vmax), end-diastolic velocity (Vmin), pulsatility index (PI), resistivity index (RI)- from the superior thyroidal artery and SWE measurements were taken from both thyroid lobes. Results: The mean age of men and women in the HT group was 44.8 and 43.4 years. The mean TSH value (normal value: 0.3-4.2 uIU/ mL) was 3.90 +/- 6.6 uIU/mL, and the anti-TPO value (normal value: < 35 IU/mL) was 235.47 +/- 271.12 IU/mL. The average thyroid gland volume was 10.12 +/- 2.71 mL in the HT group and 6.62 +/- 2.11 mL in the control group (P = 0.034). HT group mean Vmax, mean Vmin, mean PI and RI values were significantly lower compared to normal subjects (P = 0.022, P = 0.026, P = 0.042, P = 0.046, respectively). The average SWE value of the thyroid gland was 24.56 +/- 18.04 kPa in the experimental group and 7.34 +/- 3.54 (P < 0.05) in the control group. Conclusion: A positive correlation was found between PI and RI values and elastography values. An increase in SWE and decreases in Vmax and Vmin were found as high diagnostic value for HT.
Keywords: Doppler; elastography; Hashimoto; DIFFERENTIAL-DIAGNOSIS; RESISTIVE INDEX; BLOOD-FLOW; ULTRASOUND; NODULES; BENIGN